2012
DOI: 10.1093/aje/kws177
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Infection in the First Trimester of Pregnancy and Risk of Fetal Loss: A Population-based Case-Control Study

Abstract: Because parvovirus B19 infection during pregnancy has been associated with increased risk of fetal loss in small or selected study populations, the authors evaluated the risk in a population-based study. A nested case-control study was conducted by using a population-based screening for syphilis in 3 regions in Denmark from 1992 to 1994. Cases of women with fetal loss were identified in the National Patient Register (n = 2,918), and control women with live-born children were identified in the Medical Birth Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
17
0
4
Order By: Relevance
“…Fetal loss early in pregnancy has been associated with first-trimester B19V infections. In a population-based Danish study, the presence of anti-B19V IgM almost doubled the risk of fetal loss, but only 0.1% of the losses were attributable to the virus (513). In a cross-sectional study of fixed tissue from fetal loss, 6% contained B19V DNA, all in first-trimester spontaneous abortions (514).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%
“…Fetal loss early in pregnancy has been associated with first-trimester B19V infections. In a population-based Danish study, the presence of anti-B19V IgM almost doubled the risk of fetal loss, but only 0.1% of the losses were attributable to the virus (513). In a cross-sectional study of fixed tissue from fetal loss, 6% contained B19V DNA, all in first-trimester spontaneous abortions (514).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%
“…Most studies have been performed by retrospective collection of data, while only a few have been based on prospective evaluation of population cohorts. Large population-based studies to determine the burden of prenatal infections have been carried out in a few settings [302][303][304][305]. In these cases, the incidence of reported cases of B19V infection has usually been exceedingly low.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…However, this finding is different from other surveys which reported that B19V, CMV, and HSV-1/2 infections are associated with the increased risk of first-trimester spontaneous abortions [ 48 50 ]. For example, Lassen et al examined 2918 women, and found a correlation between acute B19V infection during the first trimester of pregnancy [ 49 ]. Besides, Kapranos et al reported a significant role of HSV in first-trimester spontaneous abortion, which indicated that 41 of 95 cases (43.2%) of early spontaneous abortion showed signs of HSV infection compared with 36 of 216 (16.7%) cases of elective pregnancy termination [ 51 ].…”
Section: Discussionmentioning
confidence: 99%